PERKEMBANGAN BAHASA SISWA SEKOLAH DASAR KELAS VI MIS HIDAYATUSSALAM - Syahdana, M Davy; Fitri, Destiana; Doya Zai, Frans Pratamarifai; Silvianna, Febrinata; Sinaga, Novi Novani; Tarigan, Ray Rivandi; Lase, Steven Eben Ezer (Jurnal Merah Putih Sekolah Dasar, 2023)
This study aims to determine how the language development of grade VI children at MIS HIDAYATUSSALAM. This research uses qualitative research with descriptive methods by using observation techniques in exploring relevant data. The results of this study indicate that (1) Knowing the Language Development of MIS Hidayatussalam Elementary School Students. (2) Knowing the Language Application of each character of MIS Hidayatussalam Students. (3) Knowing theproblems experienced by students in Language Development. Keywords: Development, language,Elementary School